Crossroad between obesity and gastrointestinal cancers: A review of molecular mechanisms and interventions - Moodi, Mitra; Tavakoli, Tahmineh; Tahergorabi, Zoya (International journal of preventive medicine, 2021)
The burden of gastrointestinal (GI) cancer is increasing worldwide, and in the past decade, cancer had entered the list of chronic debilitating diseases whose risk is substantially increased by hypernutrition. Obesity may increase the risk of cancer by the imbalance of various mechanisms including insulin and insulin-like growth factor1 (IGF-I) signaling, systemic inflammation, immune dysregulation, tumor angiogenesis, adipokines secretion, and intestinal microbiota that usually act interdependently. An increased understanding of the mechanisms underlying obesity-GI cancer link can provide multiple opportunities for cancer prevention. This review discusses various mechanisms involved molecular mechanisms linking obesity with GI cancers including esophagus, stomach, colorectal and hepatocellular. Furthermore, an optional intervention such as diet restriction and exercise is described, which may be preventive or therapeutic in GI cancer.